Modular Platform for Synthesis of Poly(Ionic Liquid) Electrolytes for Electrochemical Applications in Supercapacitors. Issue 15 (21st April 2021) - Kalinova, Radostina; Dimitrov, Ivaylo; Novakov, Christo; Veleva, Svetlana; Stoyanova, Antonia
Abstract: Pyrrolidinium based poly(ionic liquids) (PIL) are successfully obtained and characterized. Special attention is paid to the detailed characterization of the polymer products to determine their molecular‐mass characteristics and to establish the composition‐property relationship when selecting polymer electrolytes suitable for electrochemical tests. Characterization is performed using: chromatographic methods‐combined gel permeation chromatography (GPC) with triple detection‐refractometry, UV and laser light scattering; spectroscopy methods‐Fourier transform infrared (FTIR), proton (1H) NMR spectroscopy; thermogravimetric analysis (TGA) and TGA/gas chromatography (GC)/mass selective detection (MSD). Supercapacitors based on commercial activated carbon, with electrolyte containing PIL dissolved in dimethylformamide (DMF) have been developed and preliminary charge/discharge galvanostatic tests in a two‐electrode supercapacitor cell as well as an assessment of electrodes material and its stability in the polymeric ionic electrolyte were conducted. The PIL supercapacitor demonstrates stable capacitance characteristics and is promising for further studies in this direction. Abstract : Pyrrolidinium‐based polymer ionic liquid (PIL) with relatively low molecular mass was successfully synthesized and characterized. The applied multistep procedure resulted into a modular platform easily affording the preparation of various PILs. The electrochemical performance of symmetric supercapacitor cell using the synthesized PIL dissolved in dimethylformamide (DMF) was evaluated. The 35 % solution of PIL in DMF leads to the highest supercapacitor stability and to a high effectiveness of charge‐discharge process.